1998
DOI: 10.1124/mol.53.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Contributes to Excitotoxin-Induced Apoptosis in Rat Striatum

Abstract: Excitotoxin-induced destruction of striatal neurons, proposed as a model of Huntington's disease, involves a process having the biochemical stigmata of apoptosis. Recent studies suggested that transcription factor nuclear factor (NF)-kappa B may be involved in excitotoxicity. To further analyze the contribution of NF kappa B to excitotoxic neuronal death in vivo, changes in binding activities of NF kappa B and other transcription factors as well as the consequences of inhibiting NF kappa B nuclear translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 39 publications
6
115
0
1
Order By: Relevance
“…Third, SN50, a cell-permeable peptide carrying the nuclear localization sequence of p50 NF-B, but not mutant SN50 (SN50M) inhibits p40 2 -mediated activation of NF-B and expression of iNOS. It has been demonstrated that SN50 specifically blocks the nuclear translocation of NF-B, but does not affect the activity of AP-1, SP-1 factor, and OCT-1 transcriptional factors (48) suggesting that SN50 inhibits the expression of iNOS in p40 2 -stimulated microglial cells by inhibiting the activation of NF-B. In addition, these results also suggest that IL-12 p40 2 is biologically active and that p40 2 alone can activate microglial cells.…”
Section: Il-12 P40 Induces the Expression Of Inos Through The Activatsupporting
confidence: 62%
“…Third, SN50, a cell-permeable peptide carrying the nuclear localization sequence of p50 NF-B, but not mutant SN50 (SN50M) inhibits p40 2 -mediated activation of NF-B and expression of iNOS. It has been demonstrated that SN50 specifically blocks the nuclear translocation of NF-B, but does not affect the activity of AP-1, SP-1 factor, and OCT-1 transcriptional factors (48) suggesting that SN50 inhibits the expression of iNOS in p40 2 -stimulated microglial cells by inhibiting the activation of NF-B. In addition, these results also suggest that IL-12 p40 2 is biologically active and that p40 2 alone can activate microglial cells.…”
Section: Il-12 P40 Induces the Expression Of Inos Through The Activatsupporting
confidence: 62%
“…20 This is further supported by a recent finding that a selective peptide inhibitor of NF-kB attenuates excitotoxin-induced neuronal death in the striatum. 35 It becomes evident that necrosis is a predominant pattern of excitotoxic neuronal death according to morphology, biochemical events and interventional criteria. 18 Systemic injections of kainate into the adult rat also induced degeneration of hippocampal neurons exclusively via necrosis (q99%), marked by swelling of the cell body and mitochondria, rapid collapse of the plasma membrane and scattering of nuclear chromatin (Huh K. and Sohn S., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8] Although little is known about the mechanisms that regulate apoptotic pathways in VSMC, recent studies suggest that the transcription factor nuclear factor-B (NF B) plays a crucial role in the regulation of apoptosis. 9,10 In situ detection of nuclear p65 and p50 has revealed NF B activity within human atheroma, eg in intimal VSMC but not in undiseased arteries. 11,12 Moreover, NF B was induced in VSMC after arterial balloon injury.…”
Section: And Vcam-was Markedly Decreased In Blood Vessels Transfectedmentioning
confidence: 99%